ARABIC LOANWORD IN HAUSA AND MALAY LANGUAGE: A DESCRIPTIVE-ANALYTICAL STUDY - Abdallah , Abdallah Saleh; v, Abdul Basir; Azmi , Ummu Aiman; Abdullahi , Muhammad Sulaiman; Yusoff , Muhammad Saiful Anuar (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This descriptive-analytical study examines the systematic integration of Arabic loanwords into Hausa and Malay languages, focusing on phonological, morphological, and semantic adaptation mechanisms and their cultural implications. The research addresses a significant gap in comparative linguistics by analyzing two typologically distinct languages that have undergone extensive Arabic lexical borrowing, primarily within religious, cultural, and educational domains, with nominal categories representing the predominant borrowing pattern. Through comprehensive literature review methodology utilizing Scopus database analysis, the investigation reveals divergent adaptation strategies, i.e. Hausa demonstrates extensive morphophonological restructuring and broader functional integration across religious, educational, and daily communicative contexts, while Malay exhibits more conservative phonological assimilation patterns concentrated within religious and cultural lexicons. The findings contribute substantially to contact linguistics theory by elucidating the complex interactions between phonological and morphological systems in accommodating foreign lexical elements, while documenting how shared linguistic influence manifests differently across typologically disparate languages, thereby advancing understanding of cross-linguistic borrowing processes and their role in cultural and linguistic transformation.